An Analysis of Strategic Competence in WIUI's Podcast: NATIONALISM: Can You Love Your Country but Not Feel Proud of it? - Kirana, Dhea Aisha Chandra; Areni, Galuh Kirana Dwi (Universitas Negeri Semarang, 2025)
English speaking skill is considered an important skill as it can help people to communicate with other people around the world. However, this skill cannot be mastered by students at ease. There are many students who have encountered a lot of speaking problems, which actually can be resolved with strategic competence implementation as one of the solutions. The objectives of this study are (1) to analyze the strategic competence used in a podcast and (2) to find out the reasons for the implementation of those strategic competences by the speakers in the podcast. This research applied a descriptive qualitative approach with a content analysis method to investigate the strategic competence used in the podcast. By employing Celce-Murcia’s theory, in total, there are 253 utterances of strategic competence found in the podcast. This result revealed that there are 11 subcategories of strategic competence implemented in it, with stalling/time gaining as the most used strategy. Therefore, this research is expected to provide an understanding to the readers about the implementation of strategic competence in communication.